THE RESEARCH OF THE RAILWAY RAIL FOR ANALYSIS OF SURFACE INITIATED ROLLING CONTACT FATIGUE CRACKS - Pavlo Protsenko; Yurii Borodii; Andrii Petryshyn; Janis Thalau; Pavlo Lypovka; Eckart Uhlmann; Volodymyr Horbyk; Viktor Hlukhovskyi (Mechanics and Advanced Technologies)
Problems. Under the influence of dynamic loading from trains and natural conditions, the railway track deteriorates, characterized by the appearance of defects and residual deformations of the railway track, which lead to accelerated wear and malfunction of other elements of the rail. The appearance of the specified defects, failures and destructions of the elements of the rail grating is associated with the action of additional local stresses arising in the rails of the railway track. On a low-quality track grating with deviations of the parameters of the rail track, when the train is moving, there is an unaccounted interaction of the track and rolling stock with local overload of the interaction elements along the path. As a rule, the unaccounted interaction of track and rolling stock is accompanied by the impact of the wheel and the rail with overloading the contact area. When the impact of the wheel and rail strikes, stresses exceeding the endurance limit occur in the rail head. In this case, the rails are born in the head and begin to develop defects of contact-fatigue origin in the form of horizontal vertical and transverse cracks.